Use of air curtains on acclimatized commercial establishments: critical analysis - Neto, Luís (2008)
This article presents details on the techniques and methodologies used and results obtained in an experimental work focusing the study of the influence of various geometric and dynamic parameters on the performances of an air curtain device. The studied configurations correspond to typical aerodynamic sealing situations, applied in commercial spaces, where it is intended to keep a comfortable environment without the influence of exterior conditions. After some recommendations on selection, installation and operation, the energy and finance savings for open public spaces that use this kind of fence are estimated and some results of technical inspections conducted in commercial establishments are presented.